Exploratory study of self-regulatory learning strategies in secondary students - Wang, Monica Gek Kiang. (2008)
This study attempts to provide training in self-regulatory learning strategies, focusing on congnitive and metacognitive skills and resource management skills. The focus here is to investigate the students’ cognitive awareness of strategy use and the motivational orientation in self-efficacy and the personal effect of intellectual self-concept.